2005
DOI: 10.1007/s11119-004-0684-x
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Soil Electrical Conductivity and Terrain Attribute Variability with Soil Surveys

Abstract: Utilizing soil electrical conductivity (EC) measurements and terrain attributes for precision management will require secondary soil information for adequate interpretation. The objective of this study was to determine whether readily available second-order soil surveys were of adequate quality to aid with interpreting soil EC and terrain data. For three locations in Kentucky, USA, first-order soil surveys were created, second-order surveys reports were obtained, elevation was measured and used to calculate te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Em regiões áridas ou semi-áridas relaciona-se com a textura e o teor de sais (RHOADES et al, 1989). A RE está associada especialmente à textura e permeabilidade dos solos sob clima temperado (HARTSOCK et al, 2005). Em climas tropicais úmidos ou semi-úmidos a RE depende principalmente da saturação em água, variando substancialmente em relação às estações do ano (AUERSWALD et al, 2001).…”
Section: Resistividade Elétrica Aplicada No Estudo Pedogeomorfológicounclassified
See 1 more Smart Citation
“…Em regiões áridas ou semi-áridas relaciona-se com a textura e o teor de sais (RHOADES et al, 1989). A RE está associada especialmente à textura e permeabilidade dos solos sob clima temperado (HARTSOCK et al, 2005). Em climas tropicais úmidos ou semi-úmidos a RE depende principalmente da saturação em água, variando substancialmente em relação às estações do ano (AUERSWALD et al, 2001).…”
Section: Resistividade Elétrica Aplicada No Estudo Pedogeomorfológicounclassified
“…Em climas tropicais úmidos ou semi-úmidos a RE depende principalmente da saturação em água, variando substancialmente em relação às estações do ano (AUERSWALD et al, 2001). Recentemente, a RE é utilizada na agricultura de precisão, uma vez que pode relacionar-se com variáveis de manejo do solo por meio de funções de pedotransferência (FRAISSE et al, 2001;HARTSOCK et al, 2005 …”
Section: Resistividade Elétrica Aplicada No Estudo Pedogeomorfológicounclassified
“…However, conventional soil surveys are usually not useful for providing quantitative information about the spatial distribution of soil properties that are used in many environmental studies (Moore et al, 1993;Boer et al, 1996;Florinsky et al, 2002). Detailed soil maps that contain more information about soil properties and its spatial distribution are necessary for modern land evaluation, land suitability analysis, land resources management, land use planning, and other environmental modeling (Boer et al, 1996;Cheng et al, 1997;Zhu, 1997Zhu, , 1999Gobin et al, 2001;Park et al, 2001;Bishop et al, 2001;Hartsock et al, 2005;Salehi et al, 2003;Tomer and James, 2004;Quinn et al, 2005;Ziadat, 2005;Lark, 2007;Carre et al, 2007). Unfortunately, detailed soil maps usually cover very limited areas (Cooley, 2002;Romano and Palladino, 2002;Shi et al, 2004;Ziadat, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also topsoil sand and clay contents (Carroll and Oliver, 2005), depth to highly conductive layers and structural horizons (Tabbagh et al, 2000), and the boundary between soil and saprolite (Chaplot et al, 2001) could be identified by using electrical resistivity. The ECa maps could be related to terrain attributes alone (Hartsock et al, 2005) and in combination with depth to bedrock (Zhu et al, 2010).…”
mentioning
confidence: 99%